NUMERICAL MODELLING AND SLOPE STABILITY ANALYSIS FOR OPTIMIZING OPEN PIT COAL MINE AT BINUANG SOUTH KALIMANTAN - I GDE SURATHA (Indonesian Mining Journal, 2007)
The objective of the numerical modelling study and slope stability analysis using the finite element method (FEM) is to determine the optimum pit slope design. Many simulations were carried out by varying the overall pit slopes and the depth of the open pit coal mines. The pit slope with a safe condition in stability and a reasonable waste-coal ratio was chosen as the optimum pit slope design. According to the result of this study, some revisions on the existing pit slope design are needed. It is also recommended to develop a monitoring system, especially for instability monitoring and groundwa- ter level fluctuations behind the slope surfaces that could threaten the slope stability.